Выполнение программы развития в Украине техники и технологий сверхвысоких частот - Lugovskyy, V. V.; Nikolaenko, Yu. E.; Larkin, S. Yu. (PE "Politekhperiodika", Book and Journal Publishers, 2007)
The first results of the implementation of the state program for the development of microwave engineering in Ukraine for the years 2005–2009 are presented.